Production of the siderophore lysochelin in rich media through maltose-promoted high-density growth of Lysobacter sp. 3655 - Zhang, Fang; Liu, Jia; Jiang, Lin; Zheng, Yongbiao; Yu, Lingjun; Du, Liangcheng (Frontiers in Microbiology, 2024)
Siderophores are produced by bacteria in iron-restricted conditions. However, we found maltose could induce the biosynthesis of the siderophore lysochelin in Lysobacter sp. 3655 in rich media that are not compatible with siderophore production. Maltose markedly promoted cell growth, with over 300% increase in cell density (OD600) when LB medium was added with maltose (LBM). While lysochelin was not detectable when OD600 in LBM was below 5.0, the siderophore was clearly produced when OD600 reached 7.5 and dramatically increased when OD600 was 15.0. Coincidently, the transcription of lysochelin biosynthesis genes was remarkably enhanced following the increase of OD600. Conversely, the iron concentration in the cell culture dropped to 1.2 μM when OD600 reached 15.0, which was 6-fold lower than that in the starting medium. Moreover, mutants of the maltose-utilizing genes (orf2677 and orf2678) or quorum-sensing related gene orf644 significantly lowered the lysochelin yield. Transcriptomics analysis showed that the iron-utilizing/up-taking genes were up-regulated under high cell density. Accordingly, the transcription of lysochelin biosynthetic genes and the yield of lysochelin were stimulated when the iron-utilizing/up-taking genes were deleted. Finally, lysochelin biosynthesis was positively regulated by a TetR regulator (ORF3043). The lysochelin yield in orf3043 mutant decreased to 50% of that in the wild type and then restored in the complementary strain. Together, this study revealed a previously unrecognized mechanism for lysochelin biosynthetic regulation, by which the siderophore could still be massively produced in Lysobacter even grown in a rich culture medium. This finding could find new applications in large-scale production of 3 siderophores in bacteria.